PROFESSIONAL PRACTICES OF PR-SPECIALISTS IN SAINT PETERSBURG: A RESEARCH OF JOB SATISFACTION FACTORS - D. P. Gavra; A. S. Savitskaya; D. P. Shishkin (Дискурс, 2018)
The article is dedicated to the research of PR specialists professional practices in the context of modern hostile information environment. The authors use the qualitative methods (semi-structured narrative interviews) and try to identify and analyze the main factors of job satisfaction or dissatisfaction of PR practitioners from Saint-Petersburg. The basic hypothesis about a strong connection between job satisfaction and visible, measurable results was confirmed by analyzing full-text interview transcripts. The hypothesis that the problems of long-term PR planning and the fact of being dependant on uncontrolled external factors are the main reasons of dissatisfaction, wasn’t proved. Only one fifth of informants indicated external factors to be the reason, meanwhile two thirds described internal factors, especially the problems of communication and interaction with the management and colleagues, who misunderstand the essence and specifics of PR activity.